ROLE OF DELTA CHECK IN CLINICAL LABORATORY SERVICES - Osman Sianipar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Delta check is a process during post-analytical phases to detect discrepancies of test results before reporting by comparing current patient values to the previous test result. It is one of the efforts in assuring the quality of laboratory test results.  It has to be done although control of sampling, control of method, control of the instrument, control of reagents as well as control of data distribution has been done well. The difference between those two test results is compared to a delta check limit that is specific for the test parameter within a predefined time interval.  A time interval is flexible, and usually, most hospital laboratories choose 24 or 48 hours. Delta check limits should be defined so that both acceptable and unacceptable changes could be detected. Delta check limits should be based upon the total expected variation on both biological, and analytical variation. Delta check limits can be expressed as the absolute or percent difference between two consecutive results. The delta check system is addressed to evaluate changes in patient condition as well as quality sample issues and patient misidentification.